Dampak e-commerce bagi gen z pada usaha bisnis: Membuka peluang dan tantangan baru di era digital - Octavia, Irene Hevy (Maliki Interdisciplinary Journal, 2024)
The digital era presents e-commerce that brings major changes to the business world, including for Gen Z. E-commerce offers great opportunities for Gen Z to start and grow businesses through online platforms such as marketplaces and social media. The ease of running a business, from marketing to payment, is the main attraction. However, e-commerce also presents challenges for Gen Z. Fierce competition demands creative and innovative business strategies. Security and trust in online transactions also need to be considered. Understanding the impact of e-commerce comprehensively is key for Gen Z to seize opportunities and overcome challenges, achieving success in doing business in the digital age.